Pubertal Status Moderates the Association between Mother and Child Laboratory Pain Tolerance - Jennie CI Tsao; Ning Li; Delana Parker; Laura C Seidman; Lonnie K Zeltzer (Pain Research and Management)
BACKGROUND:There is limited information regarding the relationship between parent and child responses to laboratory pain induction in the absence of experimental manipulation.